La gestion non–durable de la steppe algérienne - Abdelkader Khaldi (VertigO)
Land of the Algerian steppe undergo a process of continuous degradation which contributed overgrazing and inadequate farming. Alteration of the natural environment (affecting both private land and common land) by the behavior of economic agents, is favored by a lack of information and existing institutions. Environmental policy in the steppe applied by the state appeared low efficiency. It is appear that sustainable use of common land requires their co-management involving state and communities.